A multilevel analysis of socioeconomic (small area) differences in household food purchasing behaviour. Issue 3 (13th February 2004) - Turrell, G; Blakely, T; Patterson, C; Oldenburg, B
Abstract : Study objective: To examine the association between area and individual level socioeconomic status (SES) and food purchasing behaviour. Design: The sample comprised 1000 households and 50 small areas. Data were collected by face to face interview (66.4% response rate). SES was measured using a composite area index of disadvantage (mean 1026.8, SD = 95.2) and household income. Purchasing behaviour was scored as continuous indices ranging from 0 to 100 for three food types: fruits (mean 50.5, SD = 17.8), vegetables (61.8, 15.2), and grocery items (51.4, 17.6), with higher scores indicating purchasing patterns more consistent with dietary guideline recommendations. Setting: Brisbane, Australia, 2000. Participants: Persons responsible for their household's food purchasing. Main results: Controlling for age, gender, and household income, a two standard deviation increase on the area SES measure was associated with a 2.01 unit increase on the fruit purchasing index (95% CI −0.49 to 4.50). The corresponding associations for vegetables and grocery foods were 0.60 (−1.36 to 2.56) and 0.94 (−1.35 to 3.23). Before controlling for household income, significant area level differences were found for each food, suggesting that clustering of household income within areas (a composition effect) accounted for the purchasing variability between them. Conclusions: Living in a socioeconomically advantaged area was associated with a tendency to purchase healthier food, however, the association was small in magnitude and the 95% CI for area SES included the null. Although urban areas in Brisbane are differentiated on the basis of their socioeconomic characteristics, it seems unlikely that where you live shapes your procurement of food over and above your personal characteristics.